Չին-եգիպտական առևտրատնտեսական համագործակցության շուրջ - Հարությունյան, Աղավնի («Զանգակ - 97»)
Egypt is the first Arab and African country to declare the establishment of diplomatic relations with China in 1956, and the first to come into strategic cooperative relations with China in 1999. Egypt signed the Deepening Bilateral Strategic and Cooperative Relations with China and memorandum which recognized the full market status of Chinese economy in 2006.
Keywords: Պատմություն; Տնտեսություն